2006
DOI: 10.1523/jneurosci.4343-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Timing of Human Visual Perception from Magnetoencephalography

Abstract: To explore the timing and the underlying neural dynamics of visual perception, we analyzed the relationship between the manual reaction time (RT) to the onset of a visual stimulus and the time course of the evoked neural response simultaneously measured by magnetoencephalography (MEG). The visual stimuli were a transition from incoherent to coherent motion of random dots and an onset of a chromatic grating from a uniform field, which evoke neural responses in different cortical sites. For both stimuli, changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 36 publications
(71 reference statements)
8
55
1
Order By: Relevance
“…As it can be observed, our results highlight the efficiency when parallel computing is used; computation times remain almost unchanged between Keeping in mind our final goal, an autonomous assistive robot, the system should provide a similar response time regardless of the task at hand, as it is the case, and, ideally, this response time should be the same as that of human beings. As our results show, the obtained response time is similar in all the studied cases (up to 50 target objects) and below 0.5 seconds, approximately twice the average human reaction time (between 200-250 milliseconds [88] [89] [90]). In the context of human-computer interaction [91] [92] [93], a response time below 0.1 second is regarded as an instantaneous reaction, whereas a response delay between 0.1 and 1.0 second is considered as fast enough for a fluent interaction, even though the user would notice the delay.…”
Section: Experiments 4: Execution Time Analysissupporting
confidence: 60%
“…As it can be observed, our results highlight the efficiency when parallel computing is used; computation times remain almost unchanged between Keeping in mind our final goal, an autonomous assistive robot, the system should provide a similar response time regardless of the task at hand, as it is the case, and, ideally, this response time should be the same as that of human beings. As our results show, the obtained response time is similar in all the studied cases (up to 50 target objects) and below 0.5 seconds, approximately twice the average human reaction time (between 200-250 milliseconds [88] [89] [90]). In the context of human-computer interaction [91] [92] [93], a response time below 0.1 second is regarded as an instantaneous reaction, whereas a response delay between 0.1 and 1.0 second is considered as fast enough for a fluent interaction, even though the user would notice the delay.…”
Section: Experiments 4: Execution Time Analysissupporting
confidence: 60%
“…3B) is reminiscent of the demonstration by Hanes et al (1995) of monotonic ramping up of firing rates of neurons in the frontal eye fields of monkeys up to the release of cued saccades. Amano et al (2006) also showed correlations of reaction time with average and single-trial magnetoencephalographic signal above occipital cortex and to a lesser extend over frontal cortex. This indicates our RT correlation results in the frontal cortex may be related to a general mechanism for releasing speeded button presses that is not particular to the task we used.…”
Section: Neuronal Correlatesmentioning
confidence: 81%
“…More recently, researchers have related measurements of electrophysiology in monkeys (Cook & Maunsell, 2002), and MEG and EEG in humans (Amano et al, 2006;Tandonnet, Burle, Hasbroucq, & Vidal, 2005;Vidal, Burle, Grapperon, & Hasbroucq, 2011) to the RTs to detect simple visual stimuli. By doing so, researchers could partition out the time needed for visual perception, which is approximately 150-200 ms.…”
Section: It Is Not Clear What the Most Appropriate Magnitude For Non-mentioning
confidence: 99%